ICT Adoption and Wage Inequality : Evidence from Mexican Firms - Iacovone, Leonardo; Pereira-Lopez, Mariana (World Bank, Washington, DC, 2018)
This paper uses a panel of firms from the Mexican Economic Censuses and analyzes at the microeconomic level how labor markets adapt to the adoption of information and communication technologies. The paper studies the effects of the adoption of information and communication technologies over the labor structure of the firm and wages. Thus, it assesses whether increasing the use of information and communication technologies leads to an increasing demand for skilled relative to low-skilled labor, and, thus, analyzes its effects on the wage gap between the two groups. The results of this analysis show that there is indeed an effect of the adoption of information and communication technologies over the demand for higher-skilled workers. However, for the manufacturing and services sectors, instead of increasing the wage gap between skilled and unskilled workers, the wage gap decreases. The results for the manufacturing sector appear to be driven by an increasing sophistication of blue-collar workers due to the organizational adjustments derived from the adoption of information and communication technologies.